Comparison Of Thermal And Optical Behaviors Of Pre-Molded And Ceramic Package Light Emitting Diodes - Lee, Zhi Yin (2013)
The project signifies thermal and optical characterizations of pre-molded and ceramic package light emitting diodes (LEDs) that are conducted by using thermal transient and light emission recording techniques. It was observed that the luminous intensity of the LEDs is dependent on the input current. However, the LEDs efficiency is reduced for about 15% with the current increases, which due to the high current density and heating of LED junction. In terms of package-level and system-level, pre-molded package LED shows approximately to 13% and 15% lower in junction-to-case and junction-to-ambient thermal resistances respectively than ceramic package LED. Despite, the heat dissipation of ceramic package LED is improved after mounting on a metal-core board (board-level). Here, the effects of packaging material properties and ratio of contacting surface area are applied. Next, the results shows that the application of thermal compound as thermal interface material yields about 6% lower junction-to-ambient thermal resistance than thermal tape. Further investigation shows that the optimum heat convection for pre-molded package LED in an open-air environment is obtained as the cooling fan facing upward; while in terms of still-air environment, it is achieved as the cooling fan facing downward. Lastly, the accuracy of the captured thermal transient is improved by considering the optical power into the determination of real thermal resistance. In sequence, it was seen that the use of direct current reveals more accurate and reliable measurement results where the occurrence of electrical disturbance is minimized.